Electronic reorganization triggered by electron transfer: The intervalence charge transfer of a Fe3+/Fe2+ bimetallic complex. Issue 11 (5th March 2015) - Domingo, Alex; Angeli, Celestino; de Graaf, Coen; Robert, Vincent
Abstract : The key role of the molecular orbitals in describing electron transfer processes is put in evidence for the intervalence charge transfer (IVCT) of a synthetic nonheme binuclear mixed‐valence Fe 3+ /Fe 2+ compound. The electronic reorganization induced by the IVCT can be quantified by controlling the adaptation of the molecular orbitals to the charge transfer process. We evaluate the transition energy and its polarization effects on the molecular orbitals by means of ab initio calculations. The resulting energetic profile of the IVCT shows strong similarities to the Marcus' model, suggesting a response behaviour of the ensemble of electrons analogue to that of the solvent. We quantify the extent of the electronic reorganization induced by the IVCT process to be 11.74 eV, a very large effect that induces the crossing of states reducing the total energy of the transfer to 0.89 eV. © 2015 Wiley Periodicals, Inc. Abstract : The electronic reorganization induced by the intervalence charge transfer of a synthetic nonheme binuclear mixed‐valence Fe 3+ /Fe 2+ complex determines the energy cost of the electron transfer. The largest electronic reorganization occurs in the pyrimidinic N atoms and the bridge O of the first coordination shell, being weaker in the metal centres. The adaptation of the molecular orbitals to the electron transfer is sufficient to inverse the spectroscopy and generate a metastable electron transfer state.